PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS PELANGGAN - Gultom, Dea Andreas Pratama; Rohman, Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
One of the concepts that can be used to increase customer loyalty is the concept of a customer-oriented company. Especially for companies engaged in services, the services provided to consumers are very crucial. One strategy that can be used to increase customer loyalty is by implementing a relationship marketing strategy. The objective of this explanatory research is to identify the effects of relationship marketing on the loyalty of Bank Sinarmas’ customers. the sample of this research is 100 respondents, selected using non-probability sampling method and purposive sampling technique. The data was analyzed using multiple linear regression analysis in SPSS 25. Relationship marketing aims to instill added values to customers to create loyalty. This study finds that trust significantly influence customer loyalty and that commitment, communication, and conflict handling do not significantly affect customer loyalty. These results indicate that the trust variable can be an additional marketing strategy for Bank Sinarmas so that it continues to encourage customers to remain loyal to Bank Sinarmas products.